Foraminiferal biostratigraphy of the upper Campanian-lower Danian of the Poty and Olinda cores in Pernambuco, northeastern Brazil - Melo, Robbyson M.; Costa, Denize Santos; Agostinho, Sonia M. O.; Koutsoukos, Eduardo A. M.; Vilela, Claudia Gutterres (Cretaceous research, 2023)
This study presents the foraminiferal biostratigraphy of the Upper Cretaceous-lower Paleogene succession of the Olinda and Poty cores in the Pernambuco-Paraíba Basin in northeastern Brazil. A total of 96 taxa of planktic foraminifera, belonging to 27 genera, that spanned the upper Campanian-lower Danian interval were recorded in this study, representing the following biozones: (1) Globotruncana aegyptiaca Interval Zone; (2) Gansserina gansseri Interval Zone; (3) Contusotruncana contusa Interval Zone; (4) Recemiguembelina fructicosa/Pseudoguembelina intermedia Interval Zone; (5) Pseudoguembelina palpebra/Pseudoguembelina hariaensis Interval Zone; (6) Plummerita hantkeninoides Interval Zone; and (7) Parvularugoglobigerina eugubina Total Range Zone/Igorina albeari Subzone (Pα-P3b). An informal subzone of benthic foraminifera, Alabamina dorsoplana/Epistomina supracretacea, was proposed for the Campanian strata in the lower part of the Gansserina gansseri Interval Zone, owing to the low recovery of planktic foraminifera in these deposits. In both core sections (Poty and Olinda), the Campanian-Maastrichtian transition was characterized by the occurrence of Pseudoguembelina palpebra. An erosive/non-depositional hiatus is recorded in the lower part of the Racemiguembelina fructicosa/Pseudoguembelina intermedia Zone within the Olinda core section. The Maastrichtian-Danian boundary is locally marked by the absence of the P0 zone, likely mixed with deposits corresponding to the Pα Zone.